Institutional Policies Affecting Needs-Driven Research in Automobile Engineering and Technology in Bayelsa State, Nigeria - Poripo (Journal of Research in Industrial Technology and Educational Studies, 2026)
The study investigated institutional policies that affects needs-driven research inAutomobile Engineering and Technology in Bayelsa State. The study adopted a descriptivesurvey research design. The study was guided by two purposes, two research questions andtwo null hypotheses were formulated to guide the study at 0.05 level of significant. Thepopulation of the study consists of 64 lecturers from 4 Higher Institutions in Bayelsa State.Data were collected using a structured questionnaire on five-point rating scale with a totalof 32 items. The questionnaire was validated by three experts to ensure its content validity.To establish reliability of the instrument, the Cronbach Alpha test was used and thereliability coefficients was 0.82, indicating that the instrument was highly reliable. Meanand Standard Deviation were used to answered the research questions. The findingsrevealed, among other things, that, misalignment of research objectives with societal andindustrial demands and bureaucratic inefficiencies were significant barriers hinderingneeds-driven research in automobile engineering and technology in Bayelsa State, Nigeria.Based on the findings, the study recommended that the government should establishnational research priorities that align with industry and academia across institutions.
Keywords: Automobile Technology; Engineering and Technology; Needs-Driven Research; institutional Policy Barriers